ANALISIS PERENCANAAN PERTUMBUHAN PRODUKSI BATU BATA DI KABUPATEN TUBAN - Latifah Anom (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2012)
This research aims to develop small industries as well as the bricks of labor, capital employed, the character of the production, supply of raw materials, and know How business feasibility, financially from small industrial brick and economic conditions around the study area. The study was conducted using descriptive methods that describe a state of population. Data is collected by observation and unstructured interviews. discussion of the results proved the brick production process is almost the same character that is labor intensive, simple technology and use their own capital, factors that positively influence the factors of the working people, working capital and fixed capital, which adversely affect the wages, extensive business and prices.